APPLYING SOME MATCHING ALGORITHMS FOR SEQUENCE IGNATURE TO ANALYZE AND DETECT ENTRIES INTO SYSTEM NETWORKS - Pham Nguyen Huy Phuong; Dang Le Nam (Tạp chí Khoa học Đại học Đà Lạt)
Nowadays, developing and evaluating pattern matching algorithms for the identification of network-attack has been constantly evolving. In this paper, the pattern matching algorithms is deployed by emulating forms of network attacks on intrusion detection system together with firewall IOS/I PS. Additionally, tools for network monitoring such as open source munintools,are also used to analyze and evaluate the performance of network-attack. Next, the time of pattern identification in the Snort's machine, and the performance of Snort as well as the number of packets passing through Snort, the amount of alerts per second, connection speed in real time, the percentage of received data in pattern matching process, etc. are also measured based on intelligent algorithms built in Snort. This aims to offer a method of choosing different algorithms for different forms of intrusion detection.